Analisis Pengaruh Endorser Personality Terhadap Brand Personality Pada Penggunaan Selebriti Dan Non-Selebriti - Tengku Firii Musfar; Arwinance Pramadewi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2010)
The result of the survey by MARS and SWA in the framework ofIndonesia Best Brand Award (IBBA) 2008 for brand performance rank in sanitarynapkins category, placed Laurier as the winner with brand value of 293.5, thencomes Softex (93.9), Charm (40.6) and Hers Protex (27.3). Meanwhile Kotex waslast inrank with brand value of 12.2 (slumped from 23.56 in 2007). Compared toits competitors, Kotex is not well known by consumers. The cause is that Kotex'sads were imable to explain its brand personality well. Charm and Hers Protexshow celebrity as endorser to strengthen their brand persona lity.The purpose of this research is to analyze the influence of endorserpersonality to brand personality, to find out the most appropriate endorser thatrepresents Kotex's personality and to analyze the comparison betweenpersonalities of celebrity and non-celebrity as Kotex's endorser.The results of this research show the influences of endorser personality tobrand personality, which are: the influence of non-celebrity endorser personalityto Kotex's brand personality nowadays, and the influence of Agnes Monicapersonality to Kotex's brand personality after treatment. It is known from dataprocessing by simple regression 1 and 2. R2 value for regression 1 is 0.466 and t-statistic value is 9.249, with 98 degree of freedom and a = 0.05 bigger than t-tablevalue 1.661. R2 value for regression 2 is 0.454 and t-statistic value is 9.031, with98 degree of freedom and a = 0.05 bigger than t-table value 1.661. Thepersonality of Kotex after treatment (with Agnes Monica as its endorser) is betterthan Kotex's personality nowadays. It is known from T test results that comparedtwo means, which are: mean for Kotex 1 (Kotex's personality nowadays) 2.8460and mean for Kotex 2 (Kotex's personality after treatment) 4.0280. Thepersonality of Agnes Monica is more positive than non-celebrity endorserpersonality. It can be seen from T test results that compared two means, whichare: endorser personality 1 (non-celebrity endorser personality) and endorserpersonality 2 (Agnes Monica personality). Mean for endorser personality 2 is4.1440 and mean for endorser personality 1 is 2.9250.